Molecular Mechanism and Pathways of Normal Human Parturition in Different Gestational Tissues: A Systematic Review of Transcriptome Studies - Ding, Wenjing; Chim, Stephen Siu Chung; Wang, Chi Chiu; Lau, Caitlyn So Ling; Leung, Tak Yeung (Frontiers in Physiology, 2021)
Objective: Genome-wide transcriptomic studies on gestational tissues in labor provide molecular insights in mechanism of normal parturition. This systematic review aimed to summarize the important genes in various gestational tissues around labor onset, and to dissect the underlying molecular regulations and pathways that trigger the labor in term pregnancies. Data sources: PubMed and Web of Science were searched from inception to January 2021. Study eligibility criteria: Untargeted genome-wide transcriptomic studies comparing the gene expression of various gestational tissues in normal term pregnant women with and without labor were included. Methods: Every differentially expressed gene was retrieved. Consistently expressed genes with same direction in different studies were identified, then gene ontology and KEGG analysis were conducted to understand molecular pathways and functions. Gene-gene association analysis was performed to determine the key regulatory gene(s) in labor onset. Results: A total of 15 studies, including 266 subjects, were included. 136, 26, 15, 7 and 3 genes were significantly changed during labor in the myometrium (7 studies, n=108), uterine cervix (4 studies, n=64), decidua (2 studies, n=42), amnion (2 studies, n=44) and placenta (2 studies, n=41), respectively. These genes were overrepresented in annotation terms related to inflammatory and immune responses. TNF and NOD-like receptor signaling pathways were overrepresented in all mentioned tissues, except the placenta. IL6 was the only gene included in both pathways, the most common reported gene in all included studies, and also the gene in the central hub of molecular regulatory network. Conclusions: This systematic review identified that genes involved in immunological and inflammatory regulations are expressed in specific gestational tissues in labor. We put forward the hypothesis that IL6 might be the key gene triggering specific mechanism in different gestational tissues, eventually leading to labor onset through inducing uterine contraction, wakening fetal membranes and stimulating cervical ripening.